Thinking ethics : how ethical values and standards are changing / edited by Beth Krasna - "Krasna, Beth (ed.)" (London, 2006)
A forceful contribution to the debate on ethics today and the likely state of ethics in ten years' time. This wide-ranging and incisive examination of the current state of ethics is also a useful signpost to likely developments over the next ten years. It is the result of five workshop discussions held in Geneva and attended by a wide range of leading international figures. Each workshop focuses on an aspect of ethics that allows the discussion to cross disciplines and cultures, producing valuable insights and assessments from the academic, business, religious, military and NGO viewpoints. Skilfully summarised by a team of experienced journalists, including Tim Hindle, business features editor of The Economist, this book provides a thoughtful, stimulating and sometimes provocative contribution to the current debate about ethics.
Keywords: Ethics